Revitalizing Producer Behavior From A Sharia Economic Perspective: an Analysis of Ethics, Objectives, and Market Balance - Khairudin, Khairudin; Suryadi, Nanda (Lembaga Penerbitan Jurnal Ilmiah Institut Agama Islam Bani Fattah Jombang, 2025)
In conventional economic systems, producers generally focus on maximizing profits through cost efficiency and increased production. However, this approach often neglects ethical considerations, social responsibility, and sustainability, leading to various issues such as economic inequality and environmental degradation. In contrast, Islamic economics views producers as khalifah who have a mandate to maintain a balance in life based on the principles of maqāṣid al-sharīʿah. This study aims to analyze the construction of producer behavior from the perspective of Islamic economics, identify the ethical principles that form the basis of Islamic production, and explain the role of Islamic producers in creating a fair and sustainable market balance. This study uses a normative approach with a library research method. The results of the study show that producer behavior in Islamic economics is not only based on profit, but also on the fulfillment of moral values, justice, and the welfare of the community. Additionally, concrete efforts are needed to revitalize the awareness of Muslim producers so they can fully apply Islamic principles in their production activities. Thus, Islamic economics is expected to become a systemic solution in addressing the challenges of a more inclusive and just modern economy.